Annual Plan 2008-09 Volume - I (General) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2008)
The State is richly endowed with natural and human resources with competitive socioeconomic advantages. It's geographical spread of 275.04 lakh Hectares accounting for 8.37% of the Country’s area makes it the 4th largest State in the country. A projected population of 8.22 Crores as on 1st March, 2008 accounting for 7.16% of country’s population makes it the 5th most populous State. During 2006-07, the net area sown was 102.39 lakh Hectares, constituting 37.2% of its geographical area. Similarly, the State has about 63.8 lakh Hectares of forest area, accounting for about 23.2% of its geographical area.
Planning Department, Government of Andhra Pradesh